If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(t + 7) = 2(2r + 7) Reorder the terms: 5(7 + t) = 2(2r + 7) (7 * 5 + t * 5) = 2(2r + 7) (35 + 5t) = 2(2r + 7) Reorder the terms: 35 + 5t = 2(7 + 2r) 35 + 5t = (7 * 2 + 2r * 2) 35 + 5t = (14 + 4r) Solving 35 + 5t = 14 + 4r Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 5t = 14 + -35 + 4r Combine like terms: 35 + -35 = 0 0 + 5t = 14 + -35 + 4r 5t = 14 + -35 + 4r Combine like terms: 14 + -35 = -21 5t = -21 + 4r Divide each side by '5'. t = -4.2 + 0.8r Simplifying t = -4.2 + 0.8r
| 5(u+5)-2= | | -x+5=6x-2 | | -5.5x+0.57=-1.64 | | .05(x+1)-1.5=9.3 | | 2x-4+2= | | (x+3)(8)=(7)(4) | | 25x+4y=25 | | -2-5x=2x-9 | | (y+6)-2y=14 | | (3m-8)(m-8)=0 | | 5x*(x+1)=15 | | 10-2x=4x-20 | | 3xy+xyz+5x-yz-xyz-3xy= | | 4/9/24/7=x | | 4(2)-3y=1 | | 2x+2x=x+10 | | 0.6(6x-9)=-34 | | 3(4)-2(5(4)+3)=14-2(4) | | 0.6x+9=-34 | | 7(-4+x)=-84 | | 8(g-5)=8 | | 4(1)-3y=1 | | 3(2x+8)+2x=56 | | z^2-2z+26=0 | | 15x-7=40 | | =75+(15+8)w | | 16=-2x+4 | | 6m+3=0 | | b=75+(15+8)w | | z-7=11 | | 25x+13=63 | | 4(0)-3y=1 |